Pengembangan Instrumen Tes Diagnostik Pilihan Ganda Tiga Tingkat (Three-Tier Test) Pada Pelajaran PAI di SD Negeri 03 Taman Agung Sumatera Selatan - Apriyadi Apriyadi; Zainul Hasan; Ade Rosad (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to describe the development process and qualitatively analyze the field-testing results of a three-tier multiple-choice diagnostic test instrument in Islamic Education (PAI). The core issue examined is the prevalence of pseudo-high scores caused by guessing techniques and latent misconceptions among students regarding abstract religious concepts. A descriptive qualitative approach was employed. Data were gathered through a combination of the three-tier diagnostic test (15 items), semi-structured interviews, participant classroom observations, and documentation review. Research participants were selected using a purposive sampling technique, comprising 25 fifth-grade students of SD Negeri 03 Taman Agung, South Sumatra, and two senior PAI teachers. Data analysis followed the Miles and Huberman interactive model. The findings revealed major themes, including "Culture-Based Misconceptions and Literalism" in purification (thaharah) materials and "Eschatological Confusion" in the doctrines of the Last Day. This instrument significantly contributes to mapping structured misconceptions that conventional tests fail to detect. In conclusion, the development of this tiered instrument provides practical implications for teachers to design precise remediation and policy implications for reforming diagnostic assessment standards at the elementary school level. Suggestions for future research include expanding the geographical scope of the study and evaluating the effectiveness of post-diagnostic intervention learning models.